Behaviour and design of composite steel and precast concrete transom for railway bridge application. (October 2019) - Mirza, O.; Talos, A.; Hennessy, M.; Kirkland, B.
Abstract: Currently most railway bridges in Australia require the frequent replacement of the timber transoms that reside in the railway system. Composite steel and precast reinforced concrete transoms have been proposed as the replacement for the current timber counterparts. This paper outlines the structural benefits of composite steel-concrete transoms for ballastless tracks when retrofitted to existing railway steel bridges. However, in existing studies, it is found that there is little investigation into the effect of derailment loading on reinforced concrete transoms. Therefore, this paper provides an investigation of derailment impact loading on precast reinforced concrete transoms. The paper herein investigates the derailment impact loading of a train through experimental testing and numerical analysis of conventional reinforced concrete transoms. The paper also evaluates the potential use of 3 different shear connectors; welded shear studs, Lindapter bolts and Ajax bolts. The results of the experimental tests and finite element models are used to determine whether each transom is a viable option for the replacement of the current timber transoms on the existing bridges in Australia and whether they provide a stronger and longer lasting solution to the current transom problem.